2013
DOI: 10.1002/mds.25326
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of myoclonus dystonia syndrome

Abstract: Myoclonus dystonia (M-D) syndrome is a heritable movement disorder characterized by myoclonic jerks and dystonia primarily of the upper extremities. M-D remains poorly responsive to pharmacological treatment. Emerging reports suggest good response to DBS of the internal globus pallidus (GPi) and ventral intermediate nucleus (VIM) of the thalamus. This study aimed to appraise the value of these two DBS targets by evaluating reports available in the literature. A systematic search of published case reports and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 31 publications
5
54
0
4
Order By: Relevance
“…The stimulation parameters are typically the same as for PD, although some patients may also respond to lower frequencies. There is growing evidence supporting the use of GPi DBS for the treatment of tardive dystonia or myoclonus dystonia [244][245][246][247][248][249][250][251][252][253][254]. Lesser and inconsistent benefit is seen in dystonia secondary to structural brain damage [255].…”
Section: Use Of Dbs For Dystoniamentioning
confidence: 99%
“…The stimulation parameters are typically the same as for PD, although some patients may also respond to lower frequencies. There is growing evidence supporting the use of GPi DBS for the treatment of tardive dystonia or myoclonus dystonia [244][245][246][247][248][249][250][251][252][253][254]. Lesser and inconsistent benefit is seen in dystonia secondary to structural brain damage [255].…”
Section: Use Of Dbs For Dystoniamentioning
confidence: 99%
“…Sodium oxybate has serious side effects, including respiratory suppression, so caution is warranted [38]. Deep brain stimulation of the thalamus or globus pallidus has had success in case reports and awaits confirmation in a larger number of patients [56].…”
Section: Myoclonus-dystonia Syndromementioning
confidence: 99%
“…The positive responses of both myoclonus and dystonia to GPi-DBS and tetrabenazine suggest that abnormal striatal signaling may be involved in the pathophysiology of M-D. A recent literature review of 40 published neurosurgically-treated cases of M-D found that improvements in myoclonus and dystonia were similar for GPi-DBS and VIM-DBS whereas improvements in dystonia were greater with GPi-DBS than VIM-DBS [4]. Compatible with these clinical findings, significantly higher levels of striatal dopamine and its metabolites were found in a knockout mouse model of M-D [9].…”
Section: Discussionmentioning
confidence: 99%
“…Myoclonus and, to a lesser degree, dystonia characteristically improve with consumption of alcohol which, in some patients, contributes to the development of alcohol dependence. More severe cases of M-D, refractory to nonsurgical treatment, may benefit from deep brain stimulation (DBS) of the internal segment of the globus pallidus (GPi) and/or ventral intermediate thalamic nucleus (VIM) [4]. …”
Section: Introductionmentioning
confidence: 99%